Заквашувальні композиції на основі мезофільних молочнокислих бактерій для простокваші - Бугера, Інна; Кігель, Наталя Федорівна (My University, 2013)
Almost no dairy products are produced from mesophilic lactic acid bacteria in Ukraine. It is so, because of the lack of modern domestic fermenting products. And so, the task of research in order to create effective starter cultures that would give characteristic curdled milk arises. We have created 12 fermenting compositions, based on mesophilic lactococcus and antagonist strain L. casei 3302. Bacterial compositions were chosen by organoleptic, physical- chemical parameters as well as the quantity of accumulated diacetyl in fermented samples As the result of the findings, it was chosen three fermenting compositions based on lactococcus and three different starter cultures of L. casei. These compositions can be used as rotational variants in production curdled milk.
Keywords: Lactococcus; кафедра біотехнології і мікробіології; fermenting; curdled milk; mesophilic lactic acid bacteria; мезофільні молочнокислі бактерії; простокваша; бродіння; брожение; мезофильные молочнокислые бактерии